First-trimester urinary extracellular vesicles as predictors of preterm birth: an insight into immune programming - Huang, Jian-Pei; Lin, Chia-Hsueh; Tseng, Chih-Wen; Chien, Ming-Hui; Lee, Hung-Chang; Yang, Kuender D. (Frontiers in Cell and Developmental Biology, 2024)
Background. The programming of innate and adaptive immunity plays a pivotal role in determining the course of pregnancy, leading to either normal term birth (TB) or preterm birth (PB) through the modulation of macrophage (M1/M2) differentiation. Extracellular vesicles (EVs) in maternal blood, harboring a repertoire of physiological and pathological messengers, are integral players in pregnancy outcomes. It is unknown whether urinary EVs (UEVs) could serve as a non-invasive mechanistic biomarker predicting PB. Methods. This study investigated first-trimester UEVs carrying M1 messengers with altered immune programming, aiming to discern their correlation to subsequent PB. A birth cohort comprising 501 pregnant women with 40 women experiencing PB, matched to 40 women experiencing TB at the same day, was examined. First-trimester UEVs were isolated for the quantification of immune mediators. Additionally, we evaluated the UEV modulation of 'trained immunity' on macrophage and lymphocyte differentiations, including mRNA expression profiles, and chromatin activation modification at histone 3 lysine 4 trimethylation (H3K4me3). Results. We found a significant elevation (p<0.05) in the particles of UEVs bearing characteristic exosome markers (CD9/CD63/CD81/Syntenin) during first-trimester of pregnancy compared to non-pregnant samples. Furthermore, UEVs from PB demonstrated significantly heightened levels of MCP-1 (p<0.003), IL-6 (p<0.041), IL-17A (p<0.007), IP-10 (p<0.036), TNF(p<0.004), IL-12 (p<0.045), and IFN (P<0.030) relative to those from TB, indicative of altered M1 and Th17 differentiation. Notably, MCP-1 (> 174 pg/ml) exhibited the sensitivity of 71.9% and specificity of 64.6%, and MCP-1 (>174 pg/ml) and IFN (> 8.7 pg/ml) provided a higher sensitivity (84.6%) of predicting PB, and moderate specificity of 66.7%. Subsequent investigations uncovered that UEVs from TB exerted a significant suppression of M1 differentiation (iNOS expression) and Th17 differentiation (RORrT expression) compared to those of PB. Conversely, UEVs derived from PB induced significantly higher expression of chromatin modification at H3K4me3 with higher production of IL-8 and TNFα cytokines (p<0.001). Implications. This pioneering study provides critical evidence for the early detection of altered M1 and Th17 responses within UEVs as a predictor of PB, and early modulation of altered M1 and Th17 polarization associated with better Treg differentiation as a potential prevention of subsequent PB.